ASEAN WAY SEBAGAI SEBUAH PARADOKS: KASUS TERORISME KELOMPOK ABU SAYYAF - Lesmana, I Made Adi; Sushanti, Sukma; Resen, Putu Titah Kawitri (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL); Vol 1 No 1 (2017), 2017)
Abu Sayyaf is a terrorist group that possibility threatens the stability and security in Southeast Asia region. Terrorist activities of the Abu Sayyaf group are not only conducted in the Philippines but also in neighboring countries. Therefore, it is necessary to handle the terrorism issue at the regional level which is through ASEAN. However, ASEAN's role in responding the Abu Sayyaf group is hampered by the ASEAN Way norms. This research analyzes how ASEAN Way hampers ASEAN cohesiveness in handling the Abu Sayyaf group. This research used qualitative method with sources of secondary data. Then, data for this research were analyzed with the concept of ASEAN Way, regionalism and foreign terrorist fighters (FTF). The main result of the research found that the elements of the ASEAN Way, namely the principle of non-intervention and consensus decision-making are hindering the ability of ASEAN to handle the Abu Sayyaf group collectively. Keywords: ASEAN, ASEAN Way, regionalism, Abu Sayyaf